Improving Assertive Behavior of Senior High School Students through Classical Guidance Based on Simulation Games - Nabila, Hurin; Setyaputri, Nora Yuniar; Basuki, Luwi Adi (IKIP Siliwangi, 2025)
This study aims to help students become more confident and courageous in expressing their opinions and desires, known as assertive behavior. The intervention was conducted through group guidance services in the classroom using simulation games. This research employed a Guidance and Counseling Action Research (PTBK) method in two cycles. The sample consisted of 42 tenth-grade students from SMA Negeri 2 Kota Kediri. Assertive behavior was measured using a Likert-scale instrument consisting of 29 statements. The collected data were analyzed descriptively to observe changes in students’ assertive behavior scores. The results showed an increase in the average assertive behavior score from 80 (moderate category) in the pre-test to 86 (moderate category) in the post-test after the first cycle. Further, they improved to 91 (high category) in the post-test after the second cycle. These findings indicate that applying simulation games through classical guidance services effectively enhances students’ assertive behavior. The implication of this study serves as a foundation for developing classical guidance programs in schools that utilize simulation games as a medium to enhance students’ assertive behavior.